2013
DOI: 10.1371/journal.pone.0068932
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Hydroxylation at the Mononuclear Nonheme Fe(II) Center of 4-(S) Hydroxymandelate Synthase – A Structure-Activity Relationship Analysis

Abstract: (S)-Hydroxymandelate synthase (Hms) is a nonheme Fe(II) dependent dioxygenase that catalyzes the oxidation of 4-hydroxyphenylpyruvate to (S)-4-hydroxymandelate by molecular oxygen. In this work, the substrate promiscuity of Hms is characterized in order to assess its potential for the biosynthesis of chiral α-hydroxy acids. Enzyme kinetic analyses, the characterization of product spectra, quantitative structure activity relationship (QSAR) analyses and in silico docking studies are used to characterize the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Hydroxymandelate synthase has been shown to catalyze a similar enzymatic reaction, via an intramolecular oxidative decarboxylation, similarly to 2KG dependent Fe(II) oxidases (26). PP_5260 is also a Fe(II)dependent decarboxylase, and the two share similar K cat values for their given substrates (330 m Ϫ1 for PP_5260 and 270 m Ϫ1 for hydroxymandelate synthase) (27). Though PP_5260 and hydroxymandelate synthase share little sequence homology, this enzyme may give us insight into the molecular mechanism of DUF1338 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxymandelate synthase has been shown to catalyze a similar enzymatic reaction, via an intramolecular oxidative decarboxylation, similarly to 2KG dependent Fe(II) oxidases (26). PP_5260 is also a Fe(II)dependent decarboxylase, and the two share similar K cat values for their given substrates (330 m Ϫ1 for PP_5260 and 270 m Ϫ1 for hydroxymandelate synthase) (27). Though PP_5260 and hydroxymandelate synthase share little sequence homology, this enzyme may give us insight into the molecular mechanism of DUF1338 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…15A). 232234 The hydroxyl group in compound 150 is then oxidized by Hmo-catalysis to produce 151 , with subsequent transamination catalyzed by HpgT leading to 4-hydroxyphenylglycine 152 (Fig. 15A), 232 which is one of the unnatural amino acids used in vancomycin 153 biosynthesis.…”
Section: Amino Acid Modificationsmentioning
confidence: 99%
“…These two enzymes share the common substrate 149, and accomplish their catalytic chemistry without requiring αKG, which is supplied from the carboxylate moiety of the substrate. 232234 The decarboxylation half-reaction of these enzymes is similar, while the other half-reactions differ in regioselectivity and complexity. A point mutant of HPPD (F337I) was shown to produce a mixture of 154 and 150 (Fig.…”
Section: Amino Acid Modificationsmentioning
confidence: 99%
“…14,15 HglS and HMS structure comparison revealed the two enzymes share a similar central β-sheet fold common to the DUF1338 structures ( Figure S2). 14,16 More importantly, the β-sheet domain of HMS contains the enzyme active site, two histidines and a glutamate that bind the metal cofactor in nearly the same orientation as in HglS. The similarity of the HglS, HMS, and HPPD folds and active sites suggested that HglS is likely an additional member of the vicinal oxygen chelate (VOC) enzyme superfamily and could act via a similar mechanism to HMS and HPPD.…”
Section: Structural Analysis Reveals the Catalytic And Specificity Mementioning
confidence: 99%
“…We had previously noted the similarity between the set of reactions catalyzed by HglS and HMS. 8,14,16 Both enzymes perform a decarboxylation-hydroxylation reaction on a α-ketoacid substrate. HPPD catalyzes a similar overall reaction with the hydroxylation occurring at a different position.…”
Section: Structural Analysis Reveals the Catalytic And Specificity Mementioning
confidence: 99%